Study of the dynamics of stress formation in glass during a thermal hardening - Shcherban, Vladyslav; Zhdanyuk, Nataliya; Plemyannikov, Mykola (Technology audit and production reserves, 2020)
The object of research is the ultimate bending strength of float glass sheet 4 mm thick. The paper confirms that the main factor affecting the increase in glass strength is the dynamics of stress formation in the surface and inner layers of glass. Rapid cooling of float glass with an air flow for 8–10 s at a rate of 25 °C/s leads to the appearance in the glass of an average temperature difference in the surface zone of 30 °C/mm. It was found that during thermal hardening at temperatures exceeding the glass transition temperature limit, there is an abrupt increase in the glass bending strength. A comparative analysis of the results of measuring the bending strength of glass for float glass and heat-strengthened glass indicates that this indicator is significantly improved. The statistical analysis of the results shows that the scatter of the values of the bending strength of annealed glass falls within the range of 30–50 MPa, and the most probable value is 40 MPa. At the same time, the spread in the values of the bending strength of thermally hardened glass is in the range of 100–160 MPa and is 135 MPa. The work proved that thermal hardening of float glass sheets increases its flexural strength by about 3.5 times. The peculiarities of the change in the type of the hardening stress diagram over time have also been studied: thermal hardening causes a more gentle course of the residual stress curve compared to hardening. In this case, the coordinate of the critical tensile stress σcrit can be located on the lower surface of the glass, which will make it possible to fracture at lower loads compared to quenching, but the fracture mechanism will be identical as for annealed glass. In this case, the destruction mechanism will be approximately the same as in the case of annealed glass, but its actual strength will be 2–3 times higher.